2022
DOI: 10.1186/s12931-022-01976-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, healthcare utilization, and related costs among patients with IPF: results from a German claims database analysis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a progressive form of fibrosing interstitial pneumonia with poor survival. This study provides insight into the epidemiology, cost, and disease course of IPF in Germany. Methods A cohort of incident patients with IPF (n = 1737) was identified from German claims data (2014–2019). Incidence and prevalence rates were calculated and adjusted for age differences compared with the overall German populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Aktuelle Studien – auch aus Deutschland – zeigen, dass nach Diagnosestellung längst nicht alle IPF-Patienten eine antifibrotische Therapie erhalten und dass die Therapieadhärenz nach 1 Jahr bei ca. 60 % liegt 15 16 . Gründe hierfür können im Einzelfall sehr hohes Alter, Multimorbidität, Pflegebedürftigkeit und prognoselimitierende Begleiterkrankungen sein; diese sollten jedoch jeweils kritisch gegenüber dem möglichen Nutzen einer Therapie abgewogen werden.…”
Section: Therapiebeginn Und Auswahl Der Substanzunclassified
“…Aktuelle Studien – auch aus Deutschland – zeigen, dass nach Diagnosestellung längst nicht alle IPF-Patienten eine antifibrotische Therapie erhalten und dass die Therapieadhärenz nach 1 Jahr bei ca. 60 % liegt 15 16 . Gründe hierfür können im Einzelfall sehr hohes Alter, Multimorbidität, Pflegebedürftigkeit und prognoselimitierende Begleiterkrankungen sein; diese sollten jedoch jeweils kritisch gegenüber dem möglichen Nutzen einer Therapie abgewogen werden.…”
Section: Therapiebeginn Und Auswahl Der Substanzunclassified
“…An array of triggers, including environmental pollutants, herbicides, drug side effects, particles, genetic abnormalities, autoimmune disorders, chronic infection, and cigarette smoking may cause IPF [ 9 , 10 , 11 , 12 ]. Nearly 200,000 people in the United States and over 5 million people worldwide are affected by IPF, and approximately 82–83% of deaths, incident cases, and prevalent cases occur in patients over 70 years old, imposing a great economic burden on the country as well as individuals [ 13 , 14 , 15 ]. A recent study from Germany showed that most patients with IPF did not receive medication [ 13 ], but previous research has demonstrated that patients who develop IPF without being treated have a median survival of only 3–5 years after diagnosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 200,000 people in the United States and over 5 million people worldwide are affected by IPF, and approximately 82–83% of deaths, incident cases, and prevalent cases occur in patients over 70 years old, imposing a great economic burden on the country as well as individuals [ 13 , 14 , 15 ]. A recent study from Germany showed that most patients with IPF did not receive medication [ 13 ], but previous research has demonstrated that patients who develop IPF without being treated have a median survival of only 3–5 years after diagnosis [ 3 ]. Consequently, there remains a major medical need for effective, safe, and well-tolerated treatments for IPF.…”
Section: Introductionmentioning
confidence: 99%